Tanzania Pre-Investment Report on Mini Hydropower Development : Case Study on the Kikuletwa River - Secsd (P) Ltd. (World Bank, Washington, DC, 2014)
The report examines three case studies in Tanzania, and presents the findings for hydropower development, based on cost-effective schemes designs, intended to benefit the country's state-owned electric power utility - TANESCO - for power generation, transmission, and distribution. The primary objective of the study is to look for economical, and reliable alternatives for meeting the growing electric power demand in different regions, particularly remote, and not yet served by the national grid. The existing local grid supply is by and large, from diesel-engine-driven generators, thus not reliable, and expensive to operate, and maintain. Each case study reviews the project area and its topographic features, surveying geological and hydrological aspects, to assess power, and energy, and civil works requirements. An economical, financial, and sensitivity analysis was conducted, and implementation costs are presented, including environmental considerations. Recommendations suggest a cascade development, consisting of small hydropower stations at the Malagarasi River; implement a series of small hydropower projects close to the demand center for the Muhuwesi River; and, a medium hydropower project close to the demand center, for the Kikuletwa River.